Fungal Cell Wall: Emerging Antifungals and Drug Resistance - Lima, Soraia L.; Colombo, Arnaldo L.; de Almeida Junior, João N. (Frontiers in Microbiology, 2019)
The cell wall is an essential component in fungal homeostasis. The lack of a covering wall in human cells make this component an attractive target for antifungal development. The host environment and antifungal stress can lead to cell wall modifications related to drug resistance. Antifungals targeting the cell wall, including the new β-D-glucan synthase inhibitor ibrexafungerp and glycosyl-phosphatidyl Inositol (GPI) anchor pathway inhibitor fosmanogepix are promising weapons against antifungal resistance. The fosmanogepix shows strong in vitro activity against the multidrug resistant species Candida auris, Fusarium solani and Lomentospora prolificans. The alternative carbon sources in the infection site changes the cell wall β-D-glucan and chitin composition, leading to echinocandin and amphotericin resistance. Candida populations that survive echinocandin exposure develop tolerance and show high chitin content in the cell wall, whilst fungal species such as Aspergillus flavus with a higher β-D-glucan content may show amphotericin resistance. Therefore understanding fungal cell dynamics has become important not only for host-fungal interactions, but also treatment of fungal infections. This review summarizes recent findings regarding antifungal therapy and development of resistance related to the fungal cell wall of the most relevant human pathogenic species.